Oncogene and non-oncogene addiction in inflammation-associated cancers. (April 2013) - Zheng, Min; Jiang, Jian; Tang, Ya-ling; Liang, Xin-hua
Many cancers originate in tissues that are chronically inflamed, and the inflammatory microenvironment is considered to promote the progression of malignancy, including initiation, growth, angiogenesis, invasion and metastasis. The molecular mechanism of inflammation-induced progression of cancers has been widely discussed. Oncogene and non-oncogene addiction have been proposed as two distinct but complementary theories to explain the initiation and development of cancers. Furthermore, they also play a role in cancer-associated inflammation. A solid understanding of oncogene and non-oncogene addiction in cancer-associated inflammatory microenvironments will help to exploit cancer drug targets for cancer prevention and clinical treatment.